Silent Signifier: Art Exhibition as a Tool of Cultural Diplomacy .......... 243 - Fadieieva, Kateryna (Oblicza dyplomacji, 2025)
Art exhibitions have emerged as potent instruments of cultural diplomacy, transcending geographical boundaries and fostering understanding among diverse communities. In an interconnected world, where communication is key, the language of art starts a universal dialogue. This paper explores the role of art exhibitions as a powerful tool for cultural diplomacy, analyzing how they facilitate the exchange of ideas, promote mutual understanding and recognition, and contribute to building bridges between nations. Art is a “silent signifier”: this term, which I have innovatively employed while investigating the topic, portraits art as a powerful and significant communicator. Cultural diplomacy is quite significant politically and socially. This is evident in the various ways which are utilized by this type of public diplomacy. Cultural diplomacy fosters global cooperation by promoting cultural exchange and building the bridges between nations, inducing greater cooperation between them, preventing, managing and mitigating conflict with the target nations.